Computer Model Development on Contact-Stabilization Wastewater Treatment Systems - Priana Sudjono; Park Sang Sook; A. Cahyo (Institute for Research and Community Services (LPPM) ITB, 2003)
Computer model is developed to relate parameters that determine the performance of a contact-stabilization system. Based on mass and substrate balance in the system, relationships between the variables are developed, then simulations using various values of the parameters can produce trend lines indicating the behavior of a system as well as the required conditions to reach an expected performance. When the operating conditions, such as recycled sludge and wasted sludge are changed, the model demonstrates alterations of the performance consistent to the developed mathematical relationships. Additionally, the computer model shows that the results could produce further explanation on phenomena of biological processes in contact-stabilization systems.